The Perpetual Impact of COVID-19 on the Geriatric Population's Quality of Life and Potential Preventive and Therapeutic Measures in Unani Medicine: An Evidence-based Review - Ara, Shabnam A.; Akhlaq, Shaheen; Ahmad, Bilal; Haque, Merajul; Fazil, Mohammad; Akram, Usama; Sayeed, Ahmad; Ali Khan, Asim (Current Traditional Medicine, 2024)
Background: COVID-19 pandemic has affected the elderly population more severely than many other patient groups. Due to their constitutional weakness and co-morbidities, geriatric populations are more prone to complications and adverse outcomes, especially with a high viral load. The Unani system of medicine encompasses several guidelines for the prevention and treatment of epidemics, which are stratified for different types of people with respect to age, geography, and health status, among others. Objective: Since Unani drugs are both safe and efficient, it has been found that demand for them has surged since COVID-19. This paper aims to discuss the various immunomodulatory, longevitypromoting agents, and organ-specific tonics specified in Unani medicine for the care of the elderly, which may be helpful during epidemics, and also, to present the scientific evidence of their efficacy. Methods: A thorough assessment of the available literature was carried out utilizing several electronic databases, including PubMed, Science Direct, Web of Science, Wiley Online, Google Scholar, and Springer Link, using the terms
Keywords: Geriatrics